Detection of Escherichia coli O157:H7 and APEC in water samples from the poultry industry - Diniz Lopes, Priscila [UNESP] (2024)
Escherichia coli are commensal bacteria and are present in the enviroNment. However, some pathotypes can cause disease in animals and humans. E. coli APEC causes colibacillosis in chickens, inducing respiratory and systemic symptoms. Enterohemorrhagic serotype O157:H7 causes foodborne infections in humans, with hemorrhagic diarrhea and hemolytic-uremic syndrome. The objective was to detect the E. coli APEC and O157:H7 serotypes in water samples from different points from the poultry production, and to evaluate the antimicrobial resistance profiles. PCR analysis was performed to detect the patterns of genes hlyF, iutA, iroN, iss and ompT from E. coli APEC and the H7 flagellar antigen and the Stx1 and Stx2 toxins from E. coli O157:H7. Thirty-three water samples from different points were positive for E. coli, among them, eight for APEC and none for O157:H7. APEC isolates showed different degrees of susceptibility to antimicrobials.